2017
DOI: 10.1111/cobi.12967
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of surrogate taxa to conserve freshwater biodiversity

Abstract: Establishing protected areas has long been an effective conservation strategy and is often basedPalabras Clave: biogeografía, diseño de reservas, planeación de la conservación, sustitutos

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Another strategy was followed by Sealey et al (2014), who estimated cumulative impact scores in coastal ecosystems due to physical restructuring, destructive uses, coastal development, and alien plant invasions, evaluating high-score areas as non-priority for conservation actions. One approach followed by some studies was to integrate alien species in the cost function of MARXAN (Hermoso et al, 2011(Hermoso et al, , 2013Lawrence et al, 2011) or ZONATION (Stewart et al, 2017), which was aimed to be minimized in the prioritization process. Specifically, Hermoso et al (2011) modeled the distribution of alien freshwater fish in the study area and used the modeled abundance as a surrogate of the cost of management actions to control invasive alien species.…”
Section: Approaches Applied To Address Biological Invasions In Consermentioning
confidence: 99%
See 1 more Smart Citation
“…Another strategy was followed by Sealey et al (2014), who estimated cumulative impact scores in coastal ecosystems due to physical restructuring, destructive uses, coastal development, and alien plant invasions, evaluating high-score areas as non-priority for conservation actions. One approach followed by some studies was to integrate alien species in the cost function of MARXAN (Hermoso et al, 2011(Hermoso et al, , 2013Lawrence et al, 2011) or ZONATION (Stewart et al, 2017), which was aimed to be minimized in the prioritization process. Specifically, Hermoso et al (2011) modeled the distribution of alien freshwater fish in the study area and used the modeled abundance as a surrogate of the cost of management actions to control invasive alien species.…”
Section: Approaches Applied To Address Biological Invasions In Consermentioning
confidence: 99%
“…Tallis et al (2008) estimated cumulative threat indices that included invasive alien species among a number of both terrestrial and marine threats, and incorporated them in the cost function of MARXAN to prioritize terrestrial and marine sites in a cross-environment conservation planning case study. Stewart et al (2017), in addition to prioritizing watersheds based on species presence, developed cost layers representing human threats (land use) and the presence of alien fish. The cost layers were used to down-weigh native species occurrences.…”
Section: Approaches Applied To Address Biological Invasions In Consermentioning
confidence: 99%
“…Our results imply that spatial‐environmental contextualization at least be carefully considered when extracting indicator species for conservation purposes, complementing other types of context study of indicator species (e.g., Tulloch et al, ). Sample classification schemes involving regionalization and typology (e.g., Herlihy, et al, ; Stoddard, ) could enhance species potential for indicating biodiversity loss/status, ecological disturbance, environmental change, and management progress (Stewart et al, ; Wiens et al, ; Zettler et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, as with any conservation surrogate (Kati et al, 2004;Lindenmayer et al, 2015), effective application of indicator species may require context. Spatial-environmental heterogeneity can make it difficult to attribute changes in ecological responses to natural versus anthropogenic forces (Fratterigo & Rusack, 2008), or to apply taxonomic surrogates for biodiversity assessment (Stewart, Underwood, Rahel, & Walters, 2018). One way to reduce the effect of heterogeneity is to stratify samples geographically or into environmentally similar groups (Stoddard, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to quantitatively identify umbrella species from among multiple candidate taxa (Caro and O'Doherty, 1999;Fleishman et al, 2000;Maslo et al, 2016;Stewart et al, 2017) often focus solely on contrasting spatial overlap identified using potentially incomplete sets of environmental predictors (Andelman and Fagan, 2000;Seddon and Leech, 2008). Despite past mixed success of using umbrella species for conservation planning (e.g., successful: Fleishman et al, 2000;Roth and Weber, 2007;Suter et al, 2002, unsuccessful: Launer andMurphy, 1994;Ozaki et al, 2006), the concept continues to improve by broadening to encompass both taxonomic and functional diversity (Sattler et al, 2014).…”
Section: Introductionmentioning
confidence: 99%